1995
DOI: 10.1257/jep.9.2.23
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immigrants on Host Country Wages, Employment and Growth

Abstract: The popular belief that immigrants have a large adverse impact on the wages and employment opportunities of the native-born population of the receiving country is not supported by the empirical evidence. A 10 percent increase in the fraction of immigrants in the population reduces native wages by 0-1 percent. Even those natives who are the closest substitutes with immigrant labor do not suffer significantly as a result of increased immigration. There is no evidence of economically significant reductions in nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
506
2
10

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 770 publications
(539 citation statements)
references
References 14 publications
12
506
2
10
Order By: Relevance
“…Second, in line with the mixed empirical evidence on the impact of immigration, many scholars have pointed out that when we move away from the FP analysis and consider more sophisticated economic models, it becomes very difficult to make clear predictions about the equilibrium effects of immigration on wages and employment opportunities among native workers (see Friedberg and Hunt 1995;Gaston the FP model, although widely taken as central in the literature, are far from general (see discussion below). 3 For general reviews about the impact of immigration on wages and employment see for example Bhagwati (2002), Borjas (1999), Card (2005), Friedberg and Hunt (1995), and Longhi, Nijkamp, and Poot (2005).…”
Section: Labor Market Competitionmentioning
confidence: 99%
“…Second, in line with the mixed empirical evidence on the impact of immigration, many scholars have pointed out that when we move away from the FP analysis and consider more sophisticated economic models, it becomes very difficult to make clear predictions about the equilibrium effects of immigration on wages and employment opportunities among native workers (see Friedberg and Hunt 1995;Gaston the FP model, although widely taken as central in the literature, are far from general (see discussion below). 3 For general reviews about the impact of immigration on wages and employment see for example Bhagwati (2002), Borjas (1999), Card (2005), Friedberg and Hunt (1995), and Longhi, Nijkamp, and Poot (2005).…”
Section: Labor Market Competitionmentioning
confidence: 99%
“…For example, a review by Friedberg and Hunt (1995) indicated that a 10-percent increase in the proportion of immigrants in the population reduced native wages by 1 percent at most. The most plausible estimates identified by Smith and Edmonston (1997) suggested that the influx of immigrants starting in 1980 had reduced the wages of high school dropouts by about 5 percent, leading them to conclude that "immigration has had only a relatively small adverse impact on the wage and employment opportunities of competing native groups" (p. 7).…”
Section: Text Box 31 Literature On Immigrants and Wages Of Nativesmentioning
confidence: 99%
“…This field distinguishes three streams of research: the economic performance of the immigrants, their effect on employment opportunities and wages of the natives and the assessment of immigration policies for host countries (surveys by Borjas (1994Borjas ( , 1999; Friedberg and Hunt (1995)). The effect of immigration on natives' wages and labor market responses are certainly the most discussed while macro-economic effects from immigration lack attention in the literature (Drinkwater et al, 2007).…”
Section: Economic Effects Of Migrationmentioning
confidence: 99%